Motivation of Prospective Science Teacher While Reading Texts as a Part of Self-Regulated Learning: Study on Critical-Argumentation Reading Activities - Bambang Subali; Siswanto Siswanto; Hartono Hartono; Masturi Masturi (Universitas Tidar, 2023)
Reading is an important activity that must be present in the science learning process, especially reading with meaningful activities, one of which is critical argumentation reading activity. Reading is very closely related to student motivation while reading. This motivation plays an important role in supporting the success of reading goals. So far, research related to students' reading motivation has rarely been carried out, especially for critical argumentation reading activities. Most of the research was conducted at the elementary and secondary school levels. Therefore, this research will be conducted with the aim of analyzing students' motivation while reading using critical argumentation activities. This study involved 83 science teacher candidate students. In practice, students were divided into three classes, namely group experimental class (N = 29), individual experimental class (N = 29), and control class (N = 25). The research was conducted using the think aloud protocol method, in which students were asked questions while reading the text, and recorded all the answers orally. The results showed that students' motivation during reading as part of a self-regulation strategy showed better results when students read using the critical argumentation reading model. In addition, students are able to carry out self-regulation strategies from a better motivational aspect if reading activities are carried out in groups.